Work Productivity through Low Back Pain among Garbage Truck Drivers in Makassar - Lestina Nurjanah; Yahya Thamrin; Syamsiar S Russeng; Masyita Muis; A. Arsunan Arsin (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Abstract. Background: Low back pain is a Musculoskeletal disorder characterized by pain in the lumbar area and is commonly experienced by workers who perform repetitive physical activities, sit for long periods, or are exposed to vibration, such as truck drivers. This condition can interfere with comfort, concentration and physical ability in carrying out tasks. As a result, Low back pain has the potential to reduce work productivity, which refers to an individual’s ability to complete tasks effectively and efficiently according to predetermined targets. Objective: To analyze the direct and indirect effects of age, duration of work, years of service, delivery frequency, BMI, vibration and working posture on work productivity through Low back pain among garbage truck drivers at the Antang Landfill. Methods: This research used a quantitative study with a cross-sectional approach and a sample size of 140 respondents obtained through purposive sampling. Data were collected using questionnaires and analyzed with SPSS. Results: Confidence Interval 95% (0,05). Indirect effects on work productivity through Low back pain were significantly shown by age (p=0.019), BMI (p=0.000), years of service (p=0.009), duration of work (p=0.009), working posture (p=0.004), delivery frequency (p=0.024) and vibration (p=0.028). Conclusion: Age, duration of work, years of service, BMI, delivery frequency, working posture and vibration have both direct and indirect effects on work productivity through Low back pain as an intervening variable.